Antimicrobial use among paediatric inpatients in a Nigerian tertiary hospital: A three-year point prevalence survey. Issue 2 (March 2023) - Umeokonkwo, Chukwuma D; Onah, Cosmas K; Adeke, Azuka S; Igwe-Okomiso, Dorothy O; Umeokonkwo, Adanna A; Madubueze, Ugochukwu C; Dauda, Saheed O; Okeke, Kingsley C; Versporten, Ann; Oduyebo, Oyinlola O; Goossens, Herman; Agu, Adaoha P
Aim: Antimicrobials are among the most widely prescribed therapeutic agents among paediatric population. Irrational use of these agents increases the risk of antimicrobial resistance. We described the prevalence and pattern of antimicrobial use among paediatric inpatients from 2017 to 2019. Subject and Method: The study was a repeated point prevalence survey over a 3-year period using the global point prevalence standardized tools among all paediatric inpatients. The prevalence of antimicrobial use, the prescription indicators and patterns of antimicrobial use were estimated. Result: Among 191 paediatric inpatients assessed, the 3-year period prevalence antimicrobial use was 85.9% (164/191) with prevalence of 80.6% in 2017, 94.6% in 2018, and 83.6% in 2019. Antimicrobial agents used ranged from one agent (20.1%) to five different agents (5.5%). Parenteral route (66.6%) was the preferred route of administration. The reason for the use of antimicrobial agents (92.6%) and the stop/review date (99.5%) were mostly well documented. Only 4.5% of the antimicrobial use were targeted. There were no antimicrobial guidelines or policy guiding the use of antimicrobial agents, except the national guideline on the treatment of malaria and tuberculosis. Ceftriaxone, a third generation cephalosporin was the most commonly used agent across the period under review. Community-acquired infection was the commonest indication for antimicrobial use. Conclusion: Our findings of high antimicrobial prevalence has raised the attention for the need to develop hospital-based antimicrobial guideline and antimicrobial stewardship program to protect the vulnerable children, their contacts and the environment from the impact of antimicrobial resistance.